2014
DOI: 10.1186/0717-6287-47-20
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extract from Vietnamese Caesalpinia sappan induces apoptosis in HeLa cells

Abstract: BackgroundThis study evaluated the cytotoxic activity of extracts from Caesalpinia sappan heartwood against multiple cancer cell lines using an MTT cell viability assay. The cell death though induction of apoptosis was as indicated by DNA fragmentation and caspase-3 enzyme activation.ResultsA methanol extract from C. sappan (MECS) showed cytotoxic activity against several of the cancer cell lines. The most potent activity exhibited by the MECS was against HeLa cells with an IC50 value of 26.5 ± 3.2 μg/mL. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Our results were agreed with the previous reports. The extract and isolated compounds, especially phenolic compounds, from C. sappan showed an ability to inhibit the growth of several cancer cells [13,23,24]. Therefore, this study presents that brazilin (1) could be a potential anticancer property against leukemia cells and reveals the first analysis of isolated compounds from C. sappan with cytotoxicity on leukemic cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were agreed with the previous reports. The extract and isolated compounds, especially phenolic compounds, from C. sappan showed an ability to inhibit the growth of several cancer cells [13,23,24]. Therefore, this study presents that brazilin (1) could be a potential anticancer property against leukemia cells and reveals the first analysis of isolated compounds from C. sappan with cytotoxicity on leukemic cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Among these compounds, brazilin (1), a homoisoflavonoid, showed the most cytotoxic effect on both leukemic cell lines. Hung et al [23] revealed that the methanol extract of C. sappan exhibited cytotoxic activity against several of the cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 activation is needed for some typical characteristic of apoptosis and is absolutely neccesary for apoptotic chromatin condensation, DNA fragmentation, and finally is one of the determinants in cancer growth and development. 17 Cancer research on microenvironment, especially the extracellular matrix is arising as a key points bringing great impact on cancer cells progression. MMPs are shown in almost all human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…By having this IC 50 value, both extracts have a relatively strong cytotoxic effect and could be further explored as an anti-cancer agent. Effect of sappan wood extract on HeLa cell give IC 50 value on 26.50 ug/mL (Hung, et al, 2014). Another study of C. sappan ethanolic extract give IC50 value of 37 ug/mL on MCF-7 cells (Khamsita, et al, 2012) and 25 uM/mL on MCF7/HER2 cells (Rahmawaty, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Study in the effect of F. septica ethanolic extract with concentration of 6 µg/mL could induce MCF7 cells into apoptosis through downregulation of BCl2 (Sekti, et al, 2010). Hung, et al (2014) reported that apoptosis in HeLa cell could be induced by methanolic extract of C. sappan with IC 50 value of 26.50 µg/mL. *Corresponding author e-mail: meiyan_e@ugm.ac.id…”
Section: Introductionmentioning
confidence: 99%